iADA : Best Practice On Alumni Web Based Information System - Sudaryono Sudaryono; Anita B Wandanaya; Fitria Indriyani (CCIT Journal, 2013)
Advances in information technology and the rapid pace of development in all sectors considered highly relevant to the relationship between computers. So spur of information technology to transform follow any changes that occur, due to the increasing needs of a growing. To some extent, there are still problems to deal with at the moment, including information regarding student alumni data are quite hard to come by society and the entire academic community colleges, thus inhibiting the activities and some decision-making. Therefore, the making of an application system that appropriate and accurate information is highly recommended. With online methods based systems, information systems alumni data will be very easy to obtain. The iADA is an information system based alumni data online are very practical. In this article describe the issues that arise as well as solving the problems examined. In addition there are three (3) characteristics and 7 (seven) advantage of this application, and the benefits of the method flowchart iADA. Featured listings on its implementation of programs written using ASP scripts. It can be concluded that the contribution of the system to maximize iADA various forms of service, and can be used as a medium of information that is valid for the entire academic community colleges and the general public.